2012
DOI: 10.1007/s00702-012-0823-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel ARC gene polymorphism is associated with reduced risk of Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is the most common neurodegenerative disease, and is clinically characterized by cognitive disturbances and the accumulation of the amyloid β (Aβ) peptides in plaques in the brain. Recent studies have shown the links between AD and the immediate-early gene Arc (activity-regulated cytoskeleton-associated protein), involved in synaptic plasticity and memory consolidation. For example, AD mouse models show a decreased expression of Arc mRNA in the brain. In additional, acute Aβ applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…A landmark study published in 2011 showed that Arc protein is required for the formation of amyloid (Aβ) plaques 80 . Moreover, Arc protein levels are aberrantly regulated in the hippocampus of AD patients 209 , and are locally upregulated around amyloid plaques 210 , whereas a polymorphism in the Arc gene confers a decreased likelihood of developing AD 211 . It has been shown that spatial memory impairment is associated with dysfunctional Arc expression in the hippocampus of an AD mouse model 212 .…”
Section: Arc Controls Synaptic Plasticity and Intrinsic Excitabilitymentioning
confidence: 99%
“…A landmark study published in 2011 showed that Arc protein is required for the formation of amyloid (Aβ) plaques 80 . Moreover, Arc protein levels are aberrantly regulated in the hippocampus of AD patients 209 , and are locally upregulated around amyloid plaques 210 , whereas a polymorphism in the Arc gene confers a decreased likelihood of developing AD 211 . It has been shown that spatial memory impairment is associated with dysfunctional Arc expression in the hippocampus of an AD mouse model 212 .…”
Section: Arc Controls Synaptic Plasticity and Intrinsic Excitabilitymentioning
confidence: 99%
“…Due to the strong links of Arc with learning and memory in healthy animals, perhaps is it not surprising that alterations in Arc and Arc-dependent synaptic plasticity are associated neuropsychiatric diseases, especially those accompanied by cognitive dysfunction. Although mutations in Arc itself are not prevalent in these diseases, dysregulation of Arc mRNA, protein levels or mutations in regulators or interacting proteins of Arc are linked with intellectual disability, autism [13, 29, 31, 104108], Alzheimer’s disease [109111], depression [60] and schizophrenia [112117]. As discussed below, alterations in mGluR-LTD and synapse elimination are associated with these diseases, and some evidence suggests this is mediated by dysregulation of Arc.…”
Section: Roles For Arc-dependent Synaptic Weakening In Neurodevelopmementioning
confidence: 99%
“…These novel findings emphasize the need to understand the physiological function of the AIS, and the implications of AIS disorder and dysfunction. Recent advances in human genetic research are essential for the advancement of psychiatric research, but may not be sufficient to understand every aspect of complex disease spectrums (19, 20). New methods to integrate gene activity and proteomic datasets, derived from biobank samples with associated clinical metadata, promise to provide the field with powerful tools to more precisely define the molecular phenotypes of psychiatric illnesses (21).…”
Section: Role Of Large-scale Genetic and Proteomics Data In Identifyimentioning
confidence: 99%